Intratumoural expression of deoxycytidylate deaminase or ribonuceotide reductase subunit M1 expression are not related to survival in patients with resected pancreatic cancer given adjuvant chemotherapy - Elander, Nils O.; Büchler, Markus W. (British journal of cancer, 2018)
Deoxycytidylate deaminase (DCTD) and ribonucleotide reductase subunit M1 (RRM1) are potential prognostic and predictive biomarkers for pyrimidine-based chemotherapy in pancreatic adenocarcinoma. Immunohistochemical staining of DCTD and RRM1 was performed on tissue microarrays representing tumour samples from 303 patients in European Study Group for Pancreatic Cancer (ESPAC)-randomised adjuvant trials following pancreatic resection, 272 of whom had received gemcitabine or 5-fluorouracil with folinic acid in ESPAC-3(v2), and 31 patients from the combined ESPAC-3(v1) and ESPAC-1 post-operative pure observational groups. Neither log-rank testing on dichotomised strata or Cox proportional hazard regression showed any relationship of DCTD or RRM1 expression levels to survival overall or by treatment group. Expression of either DCTD or RRM1 was not prognostic or predictive in patients with pancreatic adenocarcinoma who had had post-operative chemotherapy with either gemcitabine or 5-fluorouracil with folinic acid.